Peran Kurikulum Merdeka dalam Membangun Partisipasi Aktif Mahasiswa Berlandaskan Sila Ke - 4 Pancasila - Mayang Arum Rahmanita (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This research aims to determine the implementation of the independent curriculum for students in the learning process, strategies to increase students' active participation in the learning process, active participation of students in community activities and student challenges in implementing the independent curriculum. The approach to this research uses a qualitative approach by collecting data through observations and interviews about the role of the independent curriculum in building active student participation based on the 4th principle of Pancasila. The population in this study consisted of students who implemented active participation in the independent curriculum both in the learning process and community activities. Based on the research results, it shows that many students are actively involved in participation during the learning process and community activities, but the research results also show that there are still many challenges faced by students to actively participate in implementing the independent curriculum.